An Affricative Finger Print Feature Extraction Using Diagnostic Approach (International Journal of Engineering and Computer Science, 2017)
Fingerprint extraction means to find the various minutiae points in a fingerprint to use it further for fingerprint matching. But if we use the fingerprint as it is for the feature extraction then we will get a lot of minutiae points among those many arises because of noise in fingerprint and thus can’t be used for the matching of fingerprints. So we need a pre-processing technique to decrease the number of minutiae points and to get only those points that can be further used to match the fingerprint. According to experimentation results, we can decrease the number of fallacious minutiae points to a very large number by using preprocessing. In this research paper, we calculate the number of minutiae points by using three methods and then analyze the result. The comparison is between original Image and the two other pre-processed images one is obtained by using dilation operations and other is obtained by using hole filling and then dilation.